Análise das influências do sinaes na prática docente universitária. - Martins, Leandro Gonçalves (2015)
The objective of this research is to analyze the influence of the National Higher Education Evaluation System (SINAES), with emphasis on ENADE in the university teaching practice. Thus aims to understand, with a sociological interpretation, and within the context of private IES, the main influences that SINAES can bring to the university teaching practice in the perception of teachers surveyed, exposing the perception and the understanding of these on the concept and the scope of ENADE and also analyzes what these have meaning and changed their practices as a result of this external evaluation. It is considered that the interaction of teachers with ENADE can bring changes in their practices. We selected four private universities located in the city of Santos SP to be surveyed, two universities and two university centers. Participants teachers work in higher education in administration of their respective institutions. The techniques for data collection were questionnaires and interviews. Dias Sobrinho, Sguissardi and Boaventura Santos reference the Brazilian university context here reported. The sociological discourse analysis (DSA), based on Ibáñez and Ruiz Ruiz, was chosen as the analysis technique. The concepts of ethos, habitus, field and symbolic violence from Bourdieu contributed to the analysis performed in this study, seeking to better understand the words and actions of the above social context. The results show some of the perceptions that have investigated about the influences felt from the ENADE, among them stand out: limitation of the concept of ENADE the simple assessment of students; changes in the format of questions and reviews to fit the model proposed by ENADE; and even changes in the teaching plan and course contents on account of this evaluation. According to the foregoing research, can inquire about the extent to which current methods of external evaluations are adequate to ensure the quality of Brazilian higher education. Wonders about the effectiveness of ENADE beyond the quantitative purposes. Not objective conclusion, simply, if this evaluative model is good or bad for universities or teachers involved, but to present this assessment shows influences on teaching practices.